PERLINDUNGAN HUKUM TERHADAP PEMILIK ATAU PELAKU USAHA WARNET JIKA TERJADI KERUSAKAN JARINGAN DARI PENYEDIA LAYANAN INTERNET YAKNI PT. TELKOM INDONESIA - DONI ANDRIAN HSB; Maryati Bachtiar; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Internet cafes (warnet) as a form of business that can facilitate and as a place for people to connectto the internet to access and obtain all information needs, but as technology develops and changes in habitsamong people make warnet not only as a place or place to get information or just access the news, but it hasincreasingly developed into entertainment facilities with various types of entertainment such as games,music, film, fashion and others. Some people make playing / visiting an internet cafe as an inevitableroutine, habit, or activity. Internet cafe is a type of entrepreneur that rents internet services to the generalpublic, the use of internet cafe services usually starts from students, professionals, and foreign tourists.This study uses an empirical juridical approach that is an approach by looking in terms of therealities that occur in the field. While the population and sample are parties related to the problemsexamined in this study, the data sources used, primary data, secondary data, and tertiary data. Thetechnique of collecting data in this study was through interviews and literature review.From the results of the research that the authors did, it can be concluded, first legal protection forconsumers in the event of network damage that causes financial losses for some internet cafe owners is stillnot implemented, because the accountability given by Telkom only fixes the damaged equipment which is nota compensation or interpretation from compensation, based on the Consumer Protection Act and in severalArticles contained in Telkom's terms and conditions of service, also includes Articles stating providingcompensation and compensation for Service Level Guarantee that is not fulfilled or if there are differencesin the amount of the bill. The second effort made by PT. Telkom Indonesia to guarantee the rights of itsconsumers if network damage has not been carried out properly, as evidenced by the lack of fulfillment ofthe responsibilities or obligations of Telkom regarding the guarantee of its main services and appreciationto consumers when its main services suffer disruptions such as providing compensation or compensation.Keywords: Legal Protection - Internet Cafe Entrepreneurs - Network Damage.